THE ROLE OF GENE EXPRESSION ALTERATIONS, NON-CODING RNAS, COPY NUMBER VARIATIONS, AND SPLICING IN ALZHEIMER’S DISEASE - Shafee Ur Rehman; Muhammad Abdullah; Kylym Soodonbekov; Baiaman Kanatov; Saiddin Avtandil (Journal of Animal and Plant Sciences, 2025)
The neurodegenerative disorder Alzheimer’s disease (AD) advances through progressive stages, which cause cognitive deterioration and neuronal death. The study of early-onset AD shows strong connections to APP, PSEN1 and PSEN2 mutations but recent research demonstrates that multiple molecular pathways play essential roles in disease progression. The review integrates existing knowledge about four essential genetic factors that contribute to Alzheimer’s disease development: BACE1 and TREM2 expression dysregulation and, non-coding RNAs (e.g., miR-29 and BACE1-AS) and copy number variations (e.g., APP duplications and GRN deletions) and aberrant splicing events (e.g., tau 3R/4R isoform imbalance). The mechanisms work together to disrupt amyloid-beta processing and tau regulation as well as synaptic function and neuroinflammatory pathways which speed up disease progression. The review examines how these factors work together to create AD pathology while discussing their value as diagnostic markers and therapeutic targets. The review demonstrates the need for integrating multiple omics approaches to improve precision medicine approaches for diagnosing and treating Alzheimer’s disease. The review demonstrates the intricate nature of AD pathogenesis while advocating for a comprehensive strategy to understand disease mechanisms and create specific therapeutic approaches.
Keywords: Gene Expression; Non-coding RNAs; Copy Number Variations; Splicing